The Use of Milk Protein in the Production of Jelly Products - Krylova E.; Savenkova T.; Rudenko O.; Mavrina E. (Техника и технология пищевых производств)
According to the most progressive views on nutrition, the composition of food products should involve certain vital nutrients, hence the rapid development of functional, or fortified foods. An analysis of the diet of the Russian population showed a 33% lack of native proteins. Proteins serve as regulators of the genetic function of nucleic acids, participate as enzymes in all stages of the biosynthesis of polypeptides, store and transport oxygen, and perform an immunological function. The research objective was to develop a technology for producing jelly marmalade of high biological value by using milk protein. The studies were performed at the All-Russian Research Institute of the confectionery industry (a branch of V. M. Gorbatov Federal Research Center for Food Systems). The authors employed standard methods, e.g. physico-chemical, rheological, and organoleptic. The research featured jelly marmalade because it has a low nutritional value and a large amount of carbohydrates (70%). To fortify the product, the researchers used concentrated milk and whey proteins with a 80% protein content and a high biological value index (53%–170%). Gelatin served as the gelling agent. Its protein content was 87.2%. The experiment made it possible to establish the optimal ratio of sugar and molasses, the amount of gelling agent (8%), the amount of milk and whey protein concentrates (5%), and the influence of proteins on the viscosity of the jelly mass and its formation. The authors developed a method that makes it possible to introduce protein concentrates into the process of jelly boiling while preventing protein denaturation. The new technology produces jelly marmalade with milk protein content 11.2 g per 100 g, which means that the energy value of the product is 14.2%. According to regulatory documentation, such a product is deemed as a «source of protein».